Pengelolaan Zakat, Infak, dan Shadaqah oleh Lembaga Amil Zakat, Infak, dan Shadaqah Muhammadiyah (LAZISMU) Buleleng - Riska Yuliana; Naswan Suharsono (Ekuitas: Jurnal Pendidikan Ekonomi, 2021)
This research aims is to find out how the management of zakat, infaq and shadaqah by Lembaga Amil Zakat, Infaq and Shadaqah Muhammadiyah Institutions (LAZISMU) Buleleng.  This research is descriptive research. The method use in data collection is interviews, observation and documentation. Meanwhile, the data analysis technique used is data reduction, data display and conclution drawing and verification. The result of this research show and indicate that in the management of zakat, infaq and shadaqah by Lembaga Amil Zakat, Infaq and Shadaqah Muhammadiyah Institutions (LAZISMU) Buleleng has implemented the function of management, there are (planning) is implemented with determine the purposes, programs, and strategies in collecting ZIS, then (organizing) is implemented by determining the organizational structure, (actuating) is implemented with giving comparing between the result and the standart that have been made.